If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -4(6 + 6p) = -16 + -5p 8 + (6 * -4 + 6p * -4) = -16 + -5p 8 + (-24 + -24p) = -16 + -5p Combine like terms: 8 + -24 = -16 -16 + -24p = -16 + -5p Add '16' to each side of the equation. -16 + 16 + -24p = -16 + 16 + -5p Combine like terms: -16 + 16 = 0 0 + -24p = -16 + 16 + -5p -24p = -16 + 16 + -5p Combine like terms: -16 + 16 = 0 -24p = 0 + -5p -24p = -5p Solving -24p = -5p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '5p' to each side of the equation. -24p + 5p = -5p + 5p Combine like terms: -24p + 5p = -19p -19p = -5p + 5p Combine like terms: -5p + 5p = 0 -19p = 0 Divide each side by '-19'. p = 0 Simplifying p = 0
| 3p-4-6=2(p+5) | | -8b+5(b+3)=-5b+7 | | 4n-2+2n=20 | | 4x+17=9x-18 | | -17+v=-3(1-v) | | 7(y+4.5)=32.5 | | 12x^3-14x^2+1=0 | | 5x+-7=x-(-9) | | 10x+36-39x-47= | | 6x^2+40x-25=0 | | x+4=6x-51 | | 10x-7x-3=-7+2x-4 | | 9x-40=x | | 5e^2x=50 | | -36=5a+5b | | -3x-47=-5x-7 | | 0.5n+7=12 | | -123=-7(4p+1) | | -3x^2=9x | | -6(x+6)=-84 | | 5x+4=2+3x | | 4x+29=23+x | | 8m-3=9+6m | | x*74=257-(x*63) | | 2ab+3ac+6ac+4ab+ab= | | -7(-12k-3)-11=10(1+2k) | | 9=-3(e-2) | | 5p+2p-16-12=-46 | | y=ln(y) | | 6m-2=6+2m | | lny=lnx+ln(x+8)+lnC | | by+2=3c |